Adjoint methods for quasi-symmetry of vacuum fields on a surface. (21st February 2022) - Nies, Richard; Paul, Elizabeth J.; Hudson, Stuart R.; Bhattacharjee, Amitava
Abstract : Adjoint methods can speed up stellarator optimisation by providing gradient information more efficiently compared with finite-difference evaluations. Adjoint methods are herein applied to vacuum magnetic fields, with objective functions targeting quasi-symmetry and a rotational transform value on a surface. To measure quasi-symmetry, a novel way of evaluating approximate flux coordinates on a single flux surface without the assumption of a neighbourhood of flux surfaces is proposed. The shape gradients obtained from the adjoint formalism are evaluated numerically and verified against finite-difference evaluations.